(untitled) (Research, Society and Development, 2020)
Zooliterature is a term that refers to texts that cover the different forms of the animals present in literary works. The literature allows figures of speech, metaphors and stories that contribute to the construction of intellect and society. In order to carry out a critical analysis of the book Holly Cow, David Duchovny’s work, excerpts of this text were selected to provoke ethical reflection, encompass animal subjectivity and the characterization of the bovine being (bovinity), characterizing a qualitative and multidisciplinary work of literary analysis. The protagonist Elsie, a dairy cow from a small family farm starts to question her identity and the human character after learning about the world that exists outside her farm, and how farm animals are used for the benefit of the humans and the humanity. It is concluded that in this literary work written from the protagonist’s point of view, one can have a deeper view of the subjectivity of animals and the reflection of human ethics about animals, the interaction between humans and animals may be able to influence and change negatively the way of the behaviors and animalities of the humans.